Syuhada Mosque and its Community in Changing Yogyakarta, 1950s-1980s - Muhammad Yuanda Zara (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2016)
One of Yogyakarta citys symbols of colonialism is the Kotabaru region, which during the colonial period was a housing complex for Dutch ofcials and a handful of Indonesian elite. The Japanese took over the area during their Occupation. Following Indonesian independence, Indonesians seized the area for the interests of the newly born Republic of Indonesia. Syuhada Mosque, the frst modern mosque in post-independence Indonesia, was then built there, representing both Islam and Indonesian nationalism, as the mosques name and location suggest. Unlike most Indonesian mosques at the time, which were established primarily as a place for worship, Syuhada brought social and political missions. The activities of its community encompassed religious practices (such as fve obligatory daily prayers and recital of Koranic verses), handling social matters (education for children, youth and women, debate on Islam and modernity, and counter-Christianization activities), as well as responding to national politics (such as the anti-Communist movement in 1960s). Its community mostly lived outside the immediate environment of the mosque, yet Syuhada managed to present itself not just as a mosque for a small community, but for a city, even for the Indonesian nation-state. Given its four decades of overarching religious and sociopolitical functions, the mosque is deliberately aimed at a new generation of Indonesian Muslims: middle class, urban, educated, and open-minded Muslims, and serves as a role model for later mosques and religious institutions.